Teatro em comunidades: o encontro entre os artistas da Cia ZAP 18 e a comunidade do bairro Serrano e entorno - Renata Patricia da Silva (2012)
The Community Theatre is an established practice worldwide, which gives various concepts and terminologies. However, despite this diversity, some aspects are common in this discussion, which enables an understanding of the purposes that guide these practices and thus characterize them. Therefore, this paper aims to discuss how the practice developed by Cia Art Zone Periphery - ZAP 18, in partnership with the Community of the neighborhood environment Serrano and dialogues with the characteristic features of the Theatre in communities and helps to expand this discussion in Brazil . So few were privileged moments in the history of the collective, after his move to the neighborhood Serrano, outskirts of Belo Horizonte in 2002. These moments stand out, first, the noise generated in the actions of the group, due to his move to the periphery, since the environment exerts a strong influence on a practice that seeks a partnership between a group of artists and people from the local Community. Later, this group meeting with the Community of the neighborhood environment Serrano and is discussed, with reference to the actions that the group promotes in partnership with it, such as workshops and theatrical performances, which served as reference for the identification of this dialogue with aspects that Theatre featuring Communities. Therefore, it is a work that they propose to highlight some conversations and close in order to contribute to the expansion of this issue and does not fit the group's actions on pre-established standards, pointing results.